Fintech Innovation and the Transformation of Financial Service Institutions in the Digital Era - Ayesha Siddiqui; David M. Warburton (Economics Note, 2026)
Fintech innovation has emerged as a key driver of transformation in financial service institutions in the digital era. This study aims to analyze the role of fintech innovations in reshaping financial institutions, focusing on operational efficiency, financial inclusion, and competitive dynamics. The research employs a qualitative approach using a systematic literature review (SLR) of 25 recent scholarly publications from 2021–2025. The findings indicate that fintech innovations, including blockchain, artificial intelligence, digital payments, and peer-to-peer lending, significantly improve service efficiency, reduce operational costs, and enhance customer experience. However, the transformation also introduces challenges such as cybersecurity risks, regulatory gaps, and data privacy concerns. The study highlights that traditional financial institutions must adopt digital transformation strategies and collaborative models with fintech firms to remain competitive. The research contributes to the theoretical understanding of digital financial transformation and provides practical insights for policymakers and industry stakeholders.